Evaluation of sound and working memory intervention in autism spectrum disorder (ASD) children using auditory brainstem response (ABR) with psychological task - Shahrudin, Fatin Amira; Dzulkarnain, Ahmad Aidil Arafat; Jamal, Fatin Nabilah; Rahmat, Sarah; Musa, Ramli; Ahmad Basri, Nadzirah; Jusoh, Masnira; Sidek, Shahrul Naim; Md Yusof, Hazlina; Khalid, Madihah (2023)
Objective: To investigate the effectiveness of sound-working memory therapy (SWMT) in improving sensory gating (SG) of ASD children using Auditory Brainstem Response (ABR) with psychological task through Stroop task (ST).